Cadmium-induced endothelial dysfunction mediated by asymmetric dimethylarginine - Hamda A. Al-Naemi (14151675) (2020)
Cadmium (Cd) is a naturally occurring toxic heavy metal with no known essential biological functions. Exposure to Cd increases the risk of cardiovascular disease by disrupting vascular homeostasis at the endothelium. The aim of the study was to evaluate the effect of chronic low-dose Cd on vascular structure and function. Fifty adult male Sprague Dawley rats were grouped and assigned to one of two treatments for 14 weeks. The control group received normal water for 14 weeks while the Cd-treated group received 15 mg Cd/kg B.W. as CdCl2 in water for 10 weeks. A subset of the Cd-treated group received 15 mg Cd/kg B.W. as CdCl2 in water for 10 weeks followed by 4 weeks of normal water. Results show an overall decline in vascular function and structure. Withdrawal of Cd treatment showed a considerable restoration of vascular structure and vasorelaxation function. Additionally, asymmetric dimethylarginine (ADMA) bioavailability was found to be lowered over time. Interestingly, the expression of eNOS in the Cd-treated group was found to be significantly elevated during the exposure by more than 3-fold in comparison with that in the control group. This protein expression was similar to the control group after the withdrawal of Cd treatment. Taken together, the results suggest that ADMA, an eNOS inhibitor, may play a role in altering endothelial function in the presence of cadmium. In conclusion, the findings indicate that even at low doses, Cd leads to endothelial dysfunction mediated by ADMA. Other Information Published in: Environmental Science and Pollution Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11356-020-08116-5